PELAKSANAAN PROSES KEBIJAKAN JAMKESMAS DI PUSKESMAS PAL III KELURAHAN SUNGAI JAWI DALAM KECAMATAN PONTIANAK BARAT - Wahyuni E.21107007, Desy (FISIP Universitas Tanjungpura, 2013)
For years,Â Indonesia has attempted to resolve the issues of health and well-being of the community, especially among the poor. Department of Health and Local Government has developed a range of innovative strategies to improve health services more effective, efficient, and integrated. Health Insurance Program were launched by the government as a replacement Askeskin which still have not been able to be applied on target. Keep the formulation or identification that the costs incurred by society not to overburden them. Health insurance system aims to encourage the use of all the facilities and infrastructure that have been provided by the appropriate government which of course affects the financing terms of the lower and the optimal service delivery itself. Structuring the standardization of services, standardization and regulation of health care costs drug formularies should be supported by a qualified health care resources so that the calculation and analysis of the cost of any medical care that is so complex to do correctly. Of course socialization factors also take part in every step of the policy taken by the government, but at the moment this is the socialization factor that is not optimal do all health care stakeholders. Basically the health insurance system in Indonesia has always been unable to produce output where the public is increasingly aware of the rights of health care they should get.Keywords: Process Policies, Standards of Health, Human Services, Community Welfare